2015
DOI: 10.1007/s00125-015-3548-1
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure level and risk of major cardiovascular events and all-cause of mortality in patients with type 2 diabetes and renal impairment: an observational study from the Swedish National Diabetes Register

Abstract: Aims/hypothesis We assessed the relationship between BP and risk of cardiovascular events (CVEs) and all-cause mortality in patients with type 2 diabetes and renal impairment (estimated GFR<60 ml min −1 1.73 m −2 ) treated in clinical practice. Methods A total of 33,356 patients (aged 75±9 years, diabetes duration of 10±8 years) with at least one serum creatinine and BP value available in the Swedish National Diabetes Register between 2005 and 2007 were followed up until 2011 or death. The relationships betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 51 publications
4
17
0
Order By: Relevance
“…However, at a more advanced stage with concomitant systolic dysfunction, pulse pressure may drop while the risk for coronary artery events increases even further. Similarly, in a large study on patients with type 2 DM and renal impairment, the association of cardiovascular events, cardiovascular deaths and all-cause mortality with systolic BP was also J-shaped with optimal outcome at a systolic BP of 135-139 mmHg [49]. While endothelial function has been found to improve with exercise in diabetic populations [50], we did not measured this in the present study, however, pulse pressure did not improve neither in the short-nor long-term.…”
Section: Blood Pressurementioning
confidence: 84%
“…However, at a more advanced stage with concomitant systolic dysfunction, pulse pressure may drop while the risk for coronary artery events increases even further. Similarly, in a large study on patients with type 2 DM and renal impairment, the association of cardiovascular events, cardiovascular deaths and all-cause mortality with systolic BP was also J-shaped with optimal outcome at a systolic BP of 135-139 mmHg [49]. While endothelial function has been found to improve with exercise in diabetic populations [50], we did not measured this in the present study, however, pulse pressure did not improve neither in the short-nor long-term.…”
Section: Blood Pressurementioning
confidence: 84%
“…The results reflect the fact that that hypertension might complicate and increase the mortality risk among those patients with CVD, diabetes, and renal impairment, which is in accordance with results of previous studies. 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…HbA1c of 6.0% to 7.9% (42-63 mmol/ mol) were associated with lower risk of mortality in individuals aged 80 and older with diabetes mellitus, 16 which was consist with the lower risk range based on the present study. The association between low BP and higher mortality was observed in individuals with type 2 diabetes mellitus and renal impairment (mean age 75) 18 and in individuals aged 80 and older, including 25% of participants with diabetes mellitus. 26 It was shown that TC of <5.5 mmol/L tended to be associated with higher mortality, with the lowest at approximately 6 mmol/L in participants aged 80 and older.…”
Section: Main Findingsmentioning
confidence: 94%
“…10 Additional evidence has emerged from observational studies that risk of mortality is greater with low glycosylated hemoglobin (HbA1c), BP, and cholesterol in individuals with type 2 diabetes mellitus, [11][12][13][14][15] but it is uncertain whether the relationships between mortality and these cardiovascular risk factors in younger individuals can be applied to very old adults with diabetes mellitus because evidence is limited and results are inconclusive. 12,[16][17][18] This study aimed to provide new evidence by testing the hypothesis that lower HbA1c, BP, and total cholesterol (TC) are associated with lower risk of all-cause mortality in very old adults with type 2 diabetes mellitus.…”
mentioning
confidence: 99%